DARPA's explainable AI (XAI) program: A retrospective. Issue 4 (16th December 2021) - Gunning, David; Vorm, Eric; Wang, Jennifer Yunyan; Turek, Matt
Abstract : Summary of Defense Advanced Research Projects Agency's (DARPA) explainable artificial intelligence (XAI) program from the program managers' and evaluator's perspective.